Dynamic Properties and Wear Analysis of a Rail Vehicle with Wheels’ Self-Lubricating Coatings - Rafał Melnik; Andrzej Chudzikiewicz; Seweryn Koziak; Michał Opala; Ján Dižo (Communications - Scientific letters of the University of Zilina, 2021)
The problem of wheel and rail wear in railway transport generates costs of reprofiling and availability of vehicles and infrastructure. One of the possibilities of wear minimizing is decreasing of the friction coefficient in wheel-rail contact by means of lubricants. Such a solution has drawbacks from which the most crucial are: decrease of tractive/braking forces and difficulties with the precise spreading of the lubricant. These disadvantages may be avoided by modern, innovative self-lubricating coatings, applied at the production stage on the wheel flanges. The aim of the study is to investigate the effect of self-lubricating coatings on a rail vehicle’s dynamic behaviour, safety against derailment and predicted wheel wear. The numerical study was performed using the wagon multibody model with simulated self-lubricating coating on wheel flanges.